Simultaneous Quantification of Quercetin and Syringic Acid in Methanolic Extract of Leucas lavandulifolia by using Validated HPTLCDensitometric Method - Shukla, Pushpendra Kumar; Srivastava, Akanksha; Misra, Ankita; Srivastava, Sharad (Indian Journal of Pharmaceutical Education and Research, 2020)
A simple, sensitive and reliable High Performance Thin Layer Chromatography (HPTLC) method was developed for the simultaneous quantification of bioactive compounds i.e quercetin and syringic acid in Leucas lavandulifolia. Methanolic extract used on HPTLC silica gel 60 F254, 10×10 (Mark) plate for the separation and quantification of bioactive compounds by using toluene: ethyl acetate: formic acid (7: 2.5: 0.5 v/v) as mobile phase. The used mobile system gives well-resolved bands of quercetin (Rf value 0.32 ± 0.06) and syringic acid (Rf value 0.38 ± 0.05) in the extract of L. lavandulifolia. The correlation coefficient was found to be 0.987 and 0.997 with standard deviation of 667.77 and 3819.77 for quercetin and syringic acid. The accuracy of the method was confirmed by recovery studies at different levels using the standard addition method. Precision studies (both inter day and intraday) are within the standard limit, RSD (%) is less than 3%. The average recovery of quercetin and syringic acid was 100.02% and 100.13% suggesting the accurateness of the method. The quantification of quercetin and syringic carried out by using a densitometric absorption mode at 275 nm and 370 nm respectively. The developed method was validated and found to be specific, linear and accurate with precision and accuracy in the concentration range of 2.0–6.0 μg/spot for quercetin and syringic acid. Hence, simple, reproducible and selective HPTLC method has been developed for the estimation of the identified bioactive markers which may be utilized as a tool for the proper authentication and standardization of L. lavandulifolia.
Keywords: HPTLC; Leucas lavandulifolia; Quercetin; Syringic acid; DPPH; Hydroxyl; Radical-Scavenging